Hubungan Konsep Diri Dengan Prestasi Akademik Mahasiswa Semeseter 8 Program Studi S1 Keperwatan STIKes Karsa Husada Garut - Andhika Lungguh Perceka; N Ai Erlinawati; Herlin Rusyani (STIKes Karsa Husada Garut, 2022)
Human beings as people of learning become an integral part between education and individuals when studying. Education is the mechanism of all-time learning in which a person resides. In order to create conducive learning environment conditions, so that students are able to improve their competence so that they have self-control, spirituality values, ethics and commendable behavior and skills needed by students themselves and the wider community. The direction of this study is to know the relationship of self-concept with the academic achievement of undergraduate nursing students in the 8th semester of Karsa Husada Garut institute. Study method uses descriptive analytics using cross sectional techniques. This study took a population of 70 people and 70 samples were obtain using total sampling techniques. Information obtained using the Q&A instrument that has been provided, through the documentation in Kes Karsa Husada Garut. The validity test used using the correlation